Pengaruh komponen indeks pembangunan manusia (IPM) terhadap pertumbuhan ekonomi di Kota Jambi Periode 2004-2018 - Bayu Permana; Yulmardi Yulmardi; Junaidi Junaidi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of this study is to look at the development of the level of health, the level of education, the level of growth and economic growth in Jambi city and to determine the level of health, the level of education, the level of growth of economic growth in Jambi city. The method that will be used in analyzing data in this study uses descriptive and quantitative analysis methods. The data used in this study are secondary data from the 2004-2018 time series. The tool used to be published uses multiple linear regression. Based on the results of multiple linear regression analysis, it can be concluded that the health level variable has a positive and significant effect on economic growth in Jambi city. The education level variable has no influence on economic growth in Jambi city. expenditure level variables that have a negative influence on economic growth in Jambi city.